Pemaknaan Sarkasme pada Stand Up Comedy Ridwan Remin “Introduction JKT 2019” : (Analisis Semiotik Charles Sanders Pierce dalam Tayangan Youtube Ridwan Remin) - Topan Hermanto; Dra. Sari Endah Nursyamsi; Dian Sukmawati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to determine the interpretation or meaning of sarcasm conveyed by comedian Ridwan Remin in the Introduction JKT 2019 show. This study uses a qualitative approach using the semiotic analysis of Charles Sanders Peirce. Peirce categorizes the triangle theory of meaning which consists of three main elements, namely signs, objects, and interpretants. Researchers conducted an analysis of the selection of text and images related to the element of sarcasm. This research shows that the sarcasm material presented by Ridwan Remin is a reality that occurs in Ridwan Remin's life to introduce himself to the audience, he shows himself as an annoying person such as creating conflict with the audience, then introduces himself as a famous Stand up comedian, after that give his views commenting on the things that are being discussed, then talk about the realities of campus life and useless friends. To Ridwan Remin or other comedians to further mature the writing of material that has an element of sarcasm before it is presented to the audience so that unwanted things do not happen, such as offences that are brought to court.